A proven reoffending study of individuals managed under the multi-agency public protection arrangements (MAPPA) in England and Wales - Lundrigan, Samantha; Mann, Natalie; Specht, David; Kamitz, Lea C. (Frontiers in Psychology, 2024)
Past research into the effectiveness of multi-agency public protection arrangements (MAPPA) in reducing reoffending is limited. Thus, the current research aimed to evaluate proven reoffending patterns for 39,501 MAPPA managed individuals by (1) examining patterns in the timing and frequency of proven reoffending for MAPPA managed individuals; (2) examining one-, three-, and five-year proven reoffending patterns of MAPPA managed individuals by MAPPA category, age, and gender; and (3) comparing crime harm levels and recall to custody for MAPPA managed individuals pre- and post-MAPPA adoption. Taken together, our findings show that proven reoffending rates for individuals managed under MAPPA are substantially lower than those reported in proven reoffending statistics for England and Wales. This suggests that MAPPA is making a positive contribution to managing individuals convicted of sexual and violent offences. Additionally, our findings provide the best evidence to date that MAPPA management may also be effective at reducing less serious offences which do not typically involve immediate removal from society. These findings are considered in light of their theoretical and practical implications while potential limitations and avenues for future research are outlined.